THE BIBLIOMETRICS ANALYSIS OF LITERACY OF VOCATIONAL HIGH SCHOOL STUDENT IN BUILDING CONSTRUCTION EXPERTISE - Salma Maharani; Riyan Arthur; Arris Maulana (LPPM Universitas Negeri Jakarta, 2023)
This qualitative study focuses on bibliometric analysis of literacy research trends of vocational high school’s students in the Field of Building Construction. The goal is to find out the direction and projection of research using a content analysis approach with Google Scholar and Scopus databases taking the range of 2003-2023. The data search process was carried out through Publish or Perish software which then obtained 1,166 raw data with the acquisition of saturated data as much as 24 data. This study analyzes trend growth, author country/geographic location, author agency/affiliation, keywords, and author distribution. The results found that the research topic in this study rose in the range of 2008-2012 with Indonesia as a country that appeared superior, supported by the superior affiliation of the country, namely Jakarta State University, with the author on behalf of Riyan Arthur getting a superior position in this research, while keyword analysis showed that vocational literacy studies had not been discussed much, indicated by the small bubble shape, some related keywords are about literacy skills in SMK, literacy components in SMK, to the required learning support such as e-modules. So that based on the results of existing research, it can be projected that the development of research in vocational literacy in SMK in the Field of Building Construction will be in line with the dominant results that appear in every analysis that has been carried out.